Hydrolysed salmon meal as a replacement for salmon meal in practical diets for Pacific white shrimp (Litopenaeus vannamei). (22nd October 2019) - Guo, Jingping; Swanepoel, Anneleen; Reis, João; Salze, Guillaume; Rhodes, Melanie; Davis, Donald Allen
Abstract: A series of growth, feed stability and consumption trials were conducted to evaluate the efficacy of salmon by‐product in practical diets for Pacific white shrimp, Litopenaeus vannamei . This included a salmon by‐product meal (Salmon meal: SM) and a silage hydrolysate (hydrolysed salmon meal: HSM). The basal diet containing 120 g/kg SM was incrementally replaced (0. 25, 50, 75, 100%) by HSM to produce five test diets used in two trials. A sixth diet was included which evaluated gelatin supplementation (trial 1) or pH neutralization (trial 2). In trial 1, each diet was produced using two processing conditions (laboratory extruded and formed with meat grinder) and offered to shrimp in a clear water system. The results demonstrate that up to 50% of the SM can be used to replace with HSM; however, further increases resulted in reduced performance of shrimp. The addition of gelatin reduced leaching but there was limited effect of processing on leaching. There were no detectible effects of pH adjustment of the diets. Results indicated that the growth performance of shrimp has not influenced by HSM up to 60 g/kg to replace 50% of the SM in practical diets; however, higher levels resulted in significant decrease in performance.